Barbies, Goddesses, and Entrepreneurs: Discourses of Gendered Digital Embodiment in Women's Health Apps. Issue 2 (3rd April 2018) - Doshi, Marissa J.
Abstract: This study presents a qualitative analysis of mobile phone applications (apps) marketed to women for health management. Although previous research has focused on the efficacy of apps, researchers recently have begun questioning the behaviors and knowledges prioritized through technology design. In this study, feminist perspectives are used to decode how women's health apps conceptualize a healthy female subject. Results show that the healthy female subject promoted by these apps embodies three types of subject positions: (1) Barbie; (2) Earth goddess, and (3) entrepreneur. These themes fix White, middle-class, skinny, young, and fertile female bodies as the standards for health. Women are encouraged to achieve these bodies through practices of self-surveillance, disclosure, and self-advocacy, which are encouraged and normalized through routine use of apps. Thus, apps allow women to actively participate in choosing traditional subject positions, revealing the postfeminist sensibilities of this form of technology-based embodiment.